The Role of Body Organs in Cardiac Health from the Viewpoint of Avicenna - Fataneh Hashem-Dabaghian; Farshad Amini-Behbahani; Roshanak Ghods; Mahsima Abdoli (Tehran University of Medical Sciences, 2018)
Some symptoms of heart illness can be due to diseases originating from other organs. In Persian medicine (PM), this state is called participatory heart diseases. Current medical findings have found an important association between symptoms of psychiatric disorders and chest pain. Some of the other organs such as the lungs, liver, stomach, intestines and uterus have a proven effect on the heart. This relationship between the heart and other body organs has been considered by different ancient medical doctrines during a long historical period. In this article participatory heart diseases are explained from the viewpoint of Avicenna.